1990
DOI: 10.1007/bf01186089
|View full text |Cite
|
Sign up to set email alerts
|

Association between dwarfing genes ?Rht1? and ?Rht2? and resistance toSeptoria tritici Blotch in winter wheat (Triticum aestivum L. em Thell)

Abstract: Differences in levels of resistance toSeptoria tritici blotch were observed in plants with a specific height-reducing gene. When the gene 'Rht 2' was present either as an isoline or in the progeny, a higher degree of resistance was found. The most susceptible plants were observed in populations carrying the 'Rht 1' gene. Associations, as determined by phenotypic correlations, were detected betweenSeptoria tritici blotch and tall stature, late heading, and maturity. Plants having short stature, early heading, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
2
20
0
2
Order By: Relevance
“…The observed increase in intensity of Septoria spp. in different parts of the world has been attributed to the increased use of early-maturing short-strawed cultivars, caused by changes in resistance as well as changes in canopy structure and dynamics (Bahat et al, 1980;Scott et al, 1985;Baltazar et al, 1990;Eyal and Talpaz, 1990). Although crop stature gradually changed in the Netherlands between 1974 and 1986, it is unlikely that this caused the observed increase in prevalence of Septoria spp.…”
Section: Discussionmentioning
confidence: 80%
“…The observed increase in intensity of Septoria spp. in different parts of the world has been attributed to the increased use of early-maturing short-strawed cultivars, caused by changes in resistance as well as changes in canopy structure and dynamics (Bahat et al, 1980;Scott et al, 1985;Baltazar et al, 1990;Eyal and Talpaz, 1990). Although crop stature gradually changed in the Netherlands between 1974 and 1986, it is unlikely that this caused the observed increase in prevalence of Septoria spp.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, flag leaves often will emerge on early-maturing cultivars when weather is conducive for infection . Genetic linkages between earliness and susceptibility to M. graminicola also have been reported as a possible explanation for this association (Baltazar et al 1990;Rosielle and Boyd 1985). Many semidwarf wheat cultivars possess one or both of the Norin 10 height-reducing genes (Rht 1 or Rht 2 ) in their parentage (Gale et al 1981).…”
Section: Discussionmentioning
confidence: 94%
“…However, in some cases, early maturity was highly associated with susceptibility to M. graminicola (Baltazar et al 1990;Rosielle and Boyd 1985;. In regions where STB is a major problem, disease-favorable conditions with cool temperatures and rain are more probable early in the spring.…”
Section: Discussionmentioning
confidence: 97%
“…Linkage between the Rht2 dwarfing gene and resistance to Septoria tritici in wheat has been suggested by Baltazar et al (1990) who showed that isogenic lines of wheat containing the Rht1 gene were more susceptible than those with the Rht2 gene. In the present study there was no indication that isogenic lines of Maris Huntsman or Maris Widgeon containing Rht1 had more severe symptoms of FEB than those containing Rht2.…”
Section: Discussionmentioning
confidence: 99%